Front Matter - Alice G. Brand (Editor) (Journal of the Assembly for Expanded Perspectives on Learning, 1997)
Editor's Message This is the last issue of my three-year term as inaugural editor of the Journal of the Assembly for Expanded Perspectives on Learning. There is something fine for me in starting something from nothing, so to speak. What is it about the mystery, doing the truly active research that does not require a library or the internet? I always feel the fun, the risk of doing things other people do not do. That does not necessarily make me popular. But it does make me strong. Then it makes me scared which also makes me vulnerable to criticism. At the same time, maybe because the journal is new, I figured I would be less vulnerable to it. After all, I needed time to work out the wrinkles. Fine tuning would come later. I am competitive. I like being first. I also like the idea of making a modicum of difference. It may make me a curiosity. JAEPL was, for me, after all, a kind of solution to a benign problem. The capacity for us to change our mental lives, the lives of our students, is not a bad thing—even though, in so doing, we discover nothing that wasn't already there in books and in our bodies. Like the chemical basis for the salutary effects of chicken soup, we are discovering a scientific basis of some very old ideas and practices. It has become our charge, in a way, to inform the profession about how ideas in the corners of the academy (the physical and metaphysical, spiritual, emotional, therapeutic, advanced work in medicine, states of mind/consciousness) that have not been admitted to the pedagogical mainstream in composition studies pertain to the work we do. In so doing, we honor the complexity of our subject and its beginnings. I hope we continue to pursue goals of looking inward into the mind and body and outward to social and cultural experience. I hope JAEPL continues to attract not safe but innovative papers that centrist editors marginalize. I hope that our reviewers continue to focus not on what doesn't work in manuscripts but on how they might be improved; that they do not reject a paper that makes them (or the editors) uncomfortable; but rather that they recommend good ones they don't necessarily agree with. With my term as editor at its end last Spring, 1997, 1 wish to thank my exhilarating contributors and understanding authors of rejected manuscripts. I owe my sanity to an exceptional staff who kept things running smoothly. I was enriched by P. J. of Louis Heindl and Son Printers and his staff Art, Lynn, Paul, and Vicki far making my visits to the shop fun and productive, and especially typesetter Sue Schmidt for her irrepressible good will. I hope the talented staff will continue: Anne Mullin and Sharon Gibson-Groshon who I am pleased to say have an eye for quality thought, promising thought, and the aesthetics of the journal. I pass along the torch to co-editors Kristie Fleckenstein and Linda Calendrillo, both charter members of AEPL who come to the journal after having published in it. So, as not to lose momentum, I give them space to talk about their charge. It is with pleasure and honor that we begin our tenure as co-editors of JAEPL During the past three years, Alice and her staff have maintained high standards of editorial and scholarly quality, standards that we hope to preserve. They have also trailblazed new territory, inviting explorations of new connections, always centered by the belief that "the point of the probe is always in the heart of the explorer" (Bateson, Mind and Nature: A Necessary Unity, 1979). We hope to travel the path broken by Alice and by the many fine contributors to the first three volumes of the annual; we also hope to maintain the tradition of pushing the boundaries of that path a bit more, not so much to colonize but more incorporate the power of margins into our thinking. To begin that endeavor, we have chosen "Mind, Body, Spirit: Teacher Making Connections" as the theme of JAEPL's fourth annual and our first issue as co-editors. By intellectual and spiritual training, our Western culture is dualistic one. Culturally reified with Descartes' differentiation between mind (res cognitans) and body (res extensa), the division between mind, body, and spirit has consistently privileged rational mind over unruly body. Through discrimination, however, Western civilization has also split fact from value and warranted a scientific agenda that justifies the control of all things physical. Now, in the midst of ecological devastation, cultural inequities, and individual pathologies, we in the western world and in the educational community are slowly waking to the limitations of that dualism. We are coming to see the necessary unity of mind and nature. As Gregory Bateson says, "There is no mind separate from the body, no god separate from his [sic] creation." The theme of Mind, Body, Spirit: Teachers Making Connections invites further speculations on the ways in which mind, body, and spirit unite. We urge teachers to envision connections among mind, body, spirit, and their teaching and scholarship. Possible areas for consideration include such questions as: What does the healing power of writing, especially narrative, suggest for the connection between word and flesh? What are the strengths or the weaknesses of poststructuralist orientations, currently dominant in composition studies, that transform mind, body, and spirit into textualities? What do we lose or gain from such a perspective? What insights into the mind/body/spirit connection are provided by women's spirituality, especially ecofeminism? What are the methodological as well as the pedagogical implications of connections among mind, body, spirit? What are the possibilities of an embodied discourse, and what are the concomitant challenges to traditionally rigid genre demarcations? How might schema theory, the dominant paradigm in cognitive science and in reading theory, incorporate the body? Frederic Bartlett, the father of schema theory, asserts that schemata are made and unmade on the basis of a "feeling." "Feeling" is also the means by which we "turn around" on our schemata to achieve consciousness. Therefore, what role does body play in our constructions of knowledge? As always, the theme is intended to initiate thinking, not limit it. Each of the areas listed above, as well as many other topics such as ethics and kinesthetic knowing, fall within the theme of mind, body, and spirit. We urge you to consider the nature of the connections in your lives, your teaching, your writing, and respond to our call for papers at the back of this issue.